2020
DOI: 10.1380/ejssnt.2020.101
|View full text |Cite
|
Sign up to set email alerts
|

Mass Separation of Water Cluster Ion Beam Using Two Rotating Electric Fields and Sputtering of a Polymer Thin Film

Abstract: Selection of the cluster size of an ion beam is a key factor for controlling sputtering speeds or the damaged layer of polymer materials. We developed a two rotating electric fields (REFs) type of mass spectrum (MS) filter or analyzer using a novel principle. The REF-MS can continuously separate typical sizes of cluster ions by optimizing the frequencies of the REFs. In this study, we developed an electrospray ionization (ESI) gun column to optimize the cluster sizes of a water ion beam by REF-MS.Annular ring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The advantage of VES is that it can generate a finely focused ion beam from an electrospray source. The earlier research demonstrated the precise focusing of ion beams using the VES method [11].…”
Section: B Metallic Solution Ion Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of VES is that it can generate a finely focused ion beam from an electrospray source. The earlier research demonstrated the precise focusing of ion beams using the VES method [11].…”
Section: B Metallic Solution Ion Sourcementioning
confidence: 99%
“…Another mass filtering application on water cluster ion beams generated through the vacuum electrospray (VES) method was also investigated. Within 20 μm of a beam diameter, the selected water cluster ion beam drew a distinct sputtered spiral groove on a spin-coated polystyrene polymer thin film on a Si wafer [11]. VES state measurements and a REFMS-based separation were also conducted to discuss the behavior of 2-(2-butoxyethoxy) ethanol (DEGBE) as a mobile phase [12].…”
Section: Introductionmentioning
confidence: 99%